Politics and national identity in the works of Frances Burney - Donovan, Anna Caitriona (Trinity College Dublin. School of English. Discipline of English, 2023)
This thesis analyses the novels and plays of Frances Burney in order to highlight the author's engagement with political concerns of her time, including the concepts of national identity and sympathy. Groups who experienced prejudice in eighteenth century England, such as Scottish people, Roman Catholics, Jewish people, slaves and émigrés, feature in Burney's novels. This dissertation explores the full range of Burney's works, both fictional and dramatic, so as to better assess her treatment of issues surrounding national identity and the role sympathy might play in overcoming prejudice. The thesis finds that while Burney was capable of deploying national stereotypes and caricatures, she was at least equally concerned with examining the fissures within English society that mitigated against any simple view of English national identity.
APPROVED
Keywords: eighteenth-century literature; Frances Burney